2020
DOI: 10.2196/24371
|View full text |Cite
|
Sign up to set email alerts
|

Dental Treatments During the COVID-19 Pandemic in Three Hospitals in Jordan: Retrospective Study

Abstract: Background Cases of COVID-19 first emerged in December 2019. Since then, the virus has spread rapidly worldwide, with daily increases in the numbers of infections and deaths. COVID-19 spreads via airborne transmission, which renders dental treatment a potential source of virus transmission. Dental treatments require the use of handpieces, ultrasonic devices, or air–water syringes, which generate considerable amounts of aerosols. Jordan, being one of the affected countries, instituted preventive loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Aerosol and nonaerosol-generating procedures were carried out [38]. In another study by Obeidat in Jordan, they reported a ninety percent reduction in outpatient flow and mostly the patients who showed up were having endodontic cases (51.9%) [39]. Similar findings were noted during the Ebola virus outbreak when the dental procedures were restricted to emergency dental care only [40].…”
Section: Discussionmentioning
confidence: 60%
“…Aerosol and nonaerosol-generating procedures were carried out [38]. In another study by Obeidat in Jordan, they reported a ninety percent reduction in outpatient flow and mostly the patients who showed up were having endodontic cases (51.9%) [39]. Similar findings were noted during the Ebola virus outbreak when the dental procedures were restricted to emergency dental care only [40].…”
Section: Discussionmentioning
confidence: 60%
“…Intraoral radiography was the most used radiographic technique before the COVID-19 pandemic [10][11][12][13][14] because it has a lower radiation dose and higher image quality than panoramic radiography. It continues to be superior to other radiographic methods in the diagnosis of proximal caries and endodontic treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to unify the standards for all dental health care units in the national territory in challenging times [30]. Endodontic treatment accounted for almost 50% of patient load during the lockdown, for Covid-19 pandemic, compared to approximately 20% during regular days [31]. Dental professionals seem to be consistent regarding their knowledge of the incubation period of SARS-CoV-2 [32].…”
Section: Discussionmentioning
confidence: 99%